Effectiveness of care provided by an itinerant community caregiver in reducing the burden and violence of family caregivers of impaired elderly in Rio de Janeiro, Brazil: A randomized clinical trial. - Valéria Teresa Saraiva Lino; Nadia Cristina Pinheiro Rodrigues; Daniel Groisman; Soraya Atie; Luiz Antônio Bastos Camacho; Germana Perisse (PLoS ONE)
Introduction The aging population and the rise in chronic diseases are linked to a higher number of elderly individuals with impairments. These individuals often depend on family caregivers for basic daily activities, which can impose a significant burden and increase the risk of violence against them. Objective To assess the effectiveness of itinerant community caregivers (ICC) in reducing burden, depression and risk of violence among family caregivers of impaired elderly (FCIE), while also increasing their social support. Methods Randomized controlled trial with 38 pairs of elderly people and their caregivers. For six months, twice a week, the ICC spent three hours with the elderly, completing tasks given by the FCIE. The primary outcomes were reduction of at least one level in the burden, and or in the risk of violence against the elderly. The secondary outcomes were a decrease in depressive symptoms and/or an increase in social support. Multiple log binomial regression models were used to assess the relationship between the predictors and the response variables. Results In the FCIE group, most individuals providing care were women who spent over 16 hours each day in the task of caring for the impaired elderly, with most falling between the ages of 41 and 60. Over half of them were children of the elderly participants. In the intervention group, there was a significant decrease in the likelihood of violence against the elderly, with a 10-fold reduction. However, other endpoints did not present significant changes. Conclusion The involvement of an ICC in the care of impaired elderly can contribute to reducing domestic violence by FCIE.